A LITERATURE REVIEW: LOW SODIUM RESTRICTION OF PATIENTS WITH HEART FAILURE ON HOSPITAL READMISSION - Septa Meriana Lumbantoruan (Nursing Current: Jurnal Keperawatan, 2021)
Sodium restriction effect on hospital readmission in patients with heart failure (HF) has been questioned for decades. Readmission related to low sodium intake recommendations should be changed as well as mortality. A literature review is needed to summarize the effect of low sodium, especially on readmission and mortality. This literature review aimed to summarize the prevalence of hospital readmission and mortality regarding low sodium intake in patients with HF. The searching process involved four databases; MEDLINE, Embase, EBSCO Health, Cochrane was explored for experimental studies of sodium restriction. Of 77 screened citations from 2000 to 2019 invested in patients with HF, four studies were included. Four studies from four databases were included and explained and it was found that hospital readmission was the outcome of implementing sodium restriction in patients with HF. Low sodium restriction (800 mg – 1800 mg/day) results in higher hospital readmission. Moreover, 1800 mg/day of sodium was followed by higher mortality and higher sudden death in patients with HF. Low sodium restriction did not lower hospital readmission as well as mortality of patients with HF. This article provides the reason, effect, and amount of sodium restriction in patients with HF. The recommendation from this literature review is low sodium restriction has no beneficial effect on readmission and mortality in HF conditions.